Ultra‐Sonication of ZIF‐67 Crystals Results in ZIF‐67 Nano‐Flakes. Issue 18 (11th November 2016) - Beyer, Sebastian; Prinz, Carsten; Schürmann, Robin; Feldmann, Ines; Zimathies, Annett; Blocki, Anna M.; Bald, Ilko; Schneider, Rudolf J.; Emmerling, Franziska
Abstract: Zeolitic Imidazolate Frameworks (ZIFs) are crystalline materials that comprise of metal nodes and Imidazole derivatives as linkers. ZIF‐67 is often used in polymer composite materials e. g. for gas separation membranes. Post‐synthesis treatment of ZIF‐67 crystals with ultrasound leads to unforeseen plasticity that resulted in sintered ZIF‐67 and ZIF‐67 nano‐flakes. Consequently, ultrasound increases the external surface area of ZIF‐67 which might improve e. g. blending with polymers in composite materials. These new morphologies of ZIF‐67 were characterized by transmission electron, scanning electron, and atomic force microscopy. The ultrasound treatment of ZIF‐67 did not result in the formation of an amorphous framework or a meta‐stable crystal structure as indicated by powder x‐ray diffraction. In addition, ultra‐sonicated ZIF‐67 retained the high gas adsorption capacity and pore size compared to synthesized ZIF‐67. The morphological changes are hard to detect with standard analytical methods that are usually utilized for MOF characterization. These findings also suggest that sonochemical treatment of ZIFs leads to structural effects beyond increasing the amount of nucleation clusters during sono‐chemical synthesis, which is currently not addressed in the field. Abstract : Sono‐chemical treatment of Zeolitic imidazolate Framework – (ZIF‐67) induces plasticity, results in larger external surfaces and in nano‐flakes. Crystallinity, pore size and Langmuir area are not affected.